IDENTIFIKASI KETERAMPILAN PROSES SAINS DI SMKN 1 HANAU: DIAGNOSA PADA PESERTA DIDIK BARU - Vidya Setyaningrum; Amini Ikhtiyari (LPPM Universitas Muhammadiyah Muara Bungo, 2025)
Science process skills (SPS) are essential in science education as they support students in understanding scientific concepts, thinking critically, and developing problem-solving abilities. This study aims to analyze the SPS of new students at SMKN 1 Hanau, Central Kalimantan, as an initial diagnosis in science learning. The research employed a quantitative descriptive approach involving 111 new students for the 2024/2025 academic year, selected through simple random sampling. Data were collected through SPS tests, interviews, and documentation, and analyzed using descriptive statistics.The results show that students’ integrated science process skills fall into the very low category across all measured aspects: identifying and controlling variables (34.1), formulating hypotheses (33.5), defining operational definitions (31.5), graphing and data interpretation (30.2), and experimental planning (36.8). Over 90% of students were classified in the very low category for nearly all aspects, although a few students achieved high and very high categories, especially in graphing and experimental planning.In conclusion, the integrated SPS of SMKN 1 Hanau students are generally in the very low category, indicating the need for greater emphasis on developing scientific skills. This can be achieved through more interactive and inquiry-based learning that encourages students to ask scientific questions, design and conduct experiments, analyze data, and communicate findings logically and systematically.